Penggunaan Teknik Vokal Belting untuk Meminimalisir Vocal Fatigue pada Interpretasi Lagu Rapuh oleh Ainun Irsani - Bimbi Adinda Alfian; Harpang Yudha Karyawanto (Universitas Negeri Medan, 2026)
The use of vocal belting techniques is increasingly popular in Indonesian pop music because it can produce a strong, expressive, and powerful sound. However, its application has the potential to cause vocal fatigue if done without proper technique. This study explains the application of vocal belting techniques in the interpretation of the song Rapuh by Ainun Irsani as an effort to minimize the risk of vocal cord injury. The study used a qualitative descriptive method with data collection techniques through observation, documentation, and semi-structured interviews with Ainun Irsani and Adi Nugroho. Data analysis refers to the Miles, Huberman, and Saldaña model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of belting supported by breath control, resonance, body posture, articulation, and systematic vocal warm-ups can produce optimal sound quality without increasing the risk of vocal fatigue. External factors also influence the success of this technique. The research findings emphasize the importance of systematic belting technique learning by paying attention to technical, physiological, and vocal health aspects.